Wet-laid nonwoven fabric, electrolyte-reinforced membrane, and method for producing wet-laid nonwoven fabric

By employing drawn and undrawn polyarylene sulfide fibers within specific parameters, the nonwoven fabric achieves thinness, high strength, and uniform pore diameters, addressing the limitations of existing fabrics in thickness and permeability.

JP7613646B1Active Publication Date: 2025-01-15TORAY INDUSTRIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024554129
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-13
Filing Date
2024-09-05
Publication Date
2025-01-15
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Existing wet-laid nonwoven fabrics made from polyarylene sulfide fibers face challenges in achieving a thin thickness with high tensile strength and air permeability while maintaining uniform pore diameters, as they either become too thick or lose strength when reduced in basis weight.

Method used

The use of drawn and undrawn polyarylene sulfide fibers within specific diameter and aspect ratio ranges, combined with controlled basis weight and pore distribution, to enhance dispersibility and bonding, resulting in a nonwoven fabric with uniform pore diameters and improved tensile strength.

Benefits of technology

The solution achieves a thin, high-strength nonwoven fabric with uniform pore diameters and enhanced air permeability, suitable for electrolyte membrane reinforcement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613646000001
    Figure 0007613646000001
  • Figure 0007613646000002
    Figure 0007613646000002
  • Figure 0007613646000003
    Figure 0007613646000003
Patent Text Reader

Abstract

The present invention provides a wetlaid nonwoven fabric which is thin, has high strength and air permeability, and has highly uniform pore diameters. It contains stretched polyarylene sulfide fibers having an average fiber diameter of 0.3 μm or more and 3.0 μm or less, an average pore size of 0.5 μm or more and 50.0 μm or less, and a basis weight of 1.0 g / m 2 More than 8.0g / m 2 Wet nonwoven fabric.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a wetlaid nonwoven fabric, an electrolyte-reinforced membrane, and a method for producing the wetlaid nonwoven fabric. [Background technology]

[0002] Polyarylene sulfide has high heat resistance, chemical resistance, electrical insulation, and flame retardancy, as well as excellent mechanical properties and moldability, and is therefore widely used as a metal replacement material and a material that can withstand extreme environments. Taking advantage of these properties, polyarylene sulfide fibers are also used in applications such as bag filters, papermaking canvases, electrical insulating paper, battery separators, and various diaphragms. In particular, studies are being conducted to combine the characteristics of polyarylene sulfide, such as heat resistance and chemical resistance, with the characteristics of nonwoven fabric materials, such as ion permeability and gas separation, for use as a reinforcing material for electrolyte membranes, which are attracting attention as clean energy sources.

[0003] In order to improve the efficiency of the electrolyte membrane, it is necessary to reduce the thickness of the membrane, and at the same time, it is necessary to balance the thickness with mechanical strength. For this purpose, a configuration has been proposed in which an electrolyte membrane is formed on an electrolyte membrane reinforcing material. This electrolyte membrane reinforcing material is required to be thin, have high air permeability, have high mechanical strength, and have a high uniformity of pore size of the wet-laid nonwoven fabric so as not to reduce the ion permeability of the electrolyte reinforcing membrane.

[0004] In response to this problem, for example, a wet-laid nonwoven fabric for reinforcing solid polymer electrolytes, mainly composed of polyphenylene sulfide fibers, a type of polyarylene sulfide, has been proposed (Patent Document 1). It is described that unstretched polyphenylene sulfide fibers are plasticized at a lower temperature than stretched polyphenylene sulfide fibers, and therefore act as adhesive fibers to form a wet-laid nonwoven fabric with excellent mechanical strength.

[0005] Also, a wetlaid nonwoven fabric has been proposed that is excellent in gas barrier properties and ion permeability by being composed of thermoplastic fibers having an average single fiber fineness of 0.1 to 10 dtex and a specific crimp number (Patent Document 2). It is also described that the thermoplastic fibers include polyphenylene sulfide fibers (PPS).

[0006] On the other hand, polyphenylene sulfide fiber has a problem of low water retention and easy breakage during the papermaking process. Therefore, a polyphenylene sulfide wet nonwoven fabric has been proposed in which aramid fiber, which has higher water retention than polyphenylene sulfide fiber, is mixed (Patent Document 3). It is described that by including fibrillated aramid fiber, the specific surface area of ​​the fiber is improved and the number of adhesion points between the fibers is increased, resulting in a wet nonwoven fabric with strong paper strength. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2003-77494 A [Patent Document 2] JP 2016-89197 A [Patent Document 3] JP 2020-76174 A Summary of the Invention [Problem to be solved by the invention]

[0008] The technology disclosed in Patent Document 1 can obtain a polyphenylene sulfide wet nonwoven fabric with excellent mechanical strength, but there is a problem that the skeletal fibers constituting the wet nonwoven fabric are substantially thick, so the wet nonwoven fabric cannot be made thin. For example, if the wet nonwoven fabric described in the examples is made of stretched PPS fibers with a fineness of 1.1 dtex (i.e., fiber diameter of 10 μm in polyphenylene sulfide fibers) and a fineness of 2.2 dtex (i.e., fiber diameter of 14 μm in polyphenylene sulfide fibers), it is not possible to obtain a wet nonwoven fabric with a thickness of 14 μm or less. In addition, if a wet nonwoven fabric with a low basis weight is produced using fibers with a thick fiber diameter, there is a problem that the strength is extremely reduced.

[0009] Furthermore, the technology disclosed in Patent Document 2 uses thick thermoplastic fibers with a fineness of 0.1 dtex or more (i.e., polyphenylene sulfide fibers with a fiber diameter of 3.03 μm or more) and the basis weight of the nonwoven fabric is large, so the breathability of the nonwoven fabric is low. Therefore, when the nonwoven fabric is used as an electrolyte reinforcement membrane, the power generation efficiency may decrease. On the other hand, when the thickness of the nonwoven fabric is reduced, the breathability is improved, but the number of fibers constituting the wet-laid nonwoven fabric is reduced, and the strength may decrease.

[0010] In Patent Document 3, a wetlaid nonwoven fabric with high wet paper strength is obtained by mixing fibrillated aramid fibers with a polyphenylene sulfide wetlaid nonwoven fabric. However, the wetlaid nonwoven fabric has low air permeability due to the inclusion of fibrillated fibers, and the aramid fibers have low acid resistance, which reduces the chemical resistance of the wetlaid nonwoven fabric. This reduces the strength of the wetlaid nonwoven fabric, making it unsuitable as a reinforcing material for an electrolyte membrane.

[0011] An object of the present invention is to overcome the problems of the prior art and to provide a wetlaid nonwoven fabric which is thin, has high tensile strength, high air permeability and high uniformity. [Means for solving the problem]

[0012] As a result of the investigations conducted by the present inventors, it was found that in order to make a wet-laid nonwoven fabric containing polyarylene sulfide fibers thinner and improve its air permeability and tensile strength, it is effective to make the wet-laid nonwoven fabric have a low basis weight and to make the fibers that constitute it finer. On the other hand, when ultrafine fibers are used, dispersibility is reduced, such as the occurrence of aggregation between fibers in a fiber dispersion during the production of a wet-laid nonwoven fabric, and the wet-laid nonwoven fabric produced using the dispersion is prone to unevenness, particularly in a wet-laid nonwoven fabric with a low basis weight, making it difficult to obtain a wet-laid nonwoven fabric with a high uniformity in pore size.

[0013] Therefore, in order to solve the above problems, the inventors conducted intensive research and found that, by setting the average fiber diameter of the polyarylene sulfide fiber within a specific range, a wetlaid nonwoven fabric having a high uniformity in pore size and which achieves both good breathability and tensile strength can be obtained even when the fiber has a low basis weight, and thus completed the present invention.

[0014] The present invention is intended to solve the above problems, and employs the following means. (1) A stretched polyarylene sulfide fiber having an average fiber diameter of 0.3 μm or more and 3.0 μm or less, an average pore size of 0.5 μm or more and 50.0 μm or less, and a basis weight of 1.0 g / m 2 More than 8.0g / m 2 Wet nonwoven fabric. (2) The wetlaid nonwoven fabric according to (1), which contains unstretched polyarylene sulfide fibers having an average fiber diameter of 0.8 μm or more and 6.0 μm or less. (3) The aspect ratio (average fiber length / average fiber diameter) of the stretched polyarylene sulfide fiber is 800 or more and 2000 or less, The wetlaid nonwoven fabric according to (1) or (2), wherein the unstretched polyarylene sulfide fibers have an aspect ratio (average fiber length / average fiber diameter) of 400 or more and 1,800 or less. (4) The wetlaid nonwoven fabric according to any one of (1) to (3), in which, when the pore size showing the maximum peak of the pore size distribution in a pore size distribution curve is defined as Dp (nm), pores having a size of 0.9 Dp or more and 1.1 Dp or less account for 50% or more of all pores. (5) The wetlaid nonwoven fabric according to any one of (1) to (4), which has a shrinkage rate of 8.0% or less after being left to stand in an atmosphere at a temperature of 160° C. for 24 hours. (6) The wetlaid nonwoven fabric according to any one of (2) to (5), wherein the unstretched polyarylene sulfide fibers have an average fiber diameter smaller than the average fiber diameter of the stretched polyarylene sulfide fibers. (7) An electrolyte-reinforced membrane comprising the wetlaid nonwoven fabric according to any one of (1) to (6). (8) A method for producing a wetlaid nonwoven fabric according to any one of (2) to (7), comprising a step of dispersing the stretched polyarylene sulfide fibers and the unstretched polyarylene sulfide fibers in an aqueous medium to obtain a dispersion, wherein a fiber concentration in the dispersion is 1.0 ppm by mass or more and 80.0 ppm by mass or less. (9) The method for producing a wetlaid nonwoven fabric according to (8), wherein the dispersion contains a dispersant, and the concentration of the dispersant in the dispersion is 0.0010% by mass or more and 8.0% by mass or less. Effect of the Invention

[0015] According to the present invention, a wetlaid nonwoven fabric having a small thickness, high strength and air permeability, and highly uniform pore size can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The wetlaid nonwoven fabric of the present invention satisfies the following requirements.

[0017] It contains stretched polyarylene sulfide fibers having an average fiber diameter of 0.3 μm or more and 3.0 μm or less, an average pore size of 0.5 μm or more and 50.0 μm or less, and a basis weight of 1.0 g / m 2 More than 8.0g / m 2 is less than.

[0018] The present invention will be described in detail below, but the present invention is not limited to the scope of the following description as long as it does not deviate from the gist of the present invention.

[0019] <Polyarylene sulfide fiber> The polyarylene sulfide used in the polyarylene sulfide fiber is a homopolymer or copolymer having a repeating unit of -(Ar-S)-, where Ar includes structural units represented by the following formulas (1) to (12), etc.

[0020] [ka]

[0021] [ka]

[0022] [ka]

[0023] [ka]

[0024] [ka]

[0025] [ka]

[0026] [ka]

[0027] [ka]

[0028] [ka]

[0029] [ka]

[0030] [ka]

[0031] [ka]

[0032] (In formulas (1) to (10), R 1 , R 2 are each a substituent selected from a hydrogen atom, an alkyl group, an alkoxy group, and a halogen group, and R 1 and R 2 may be the same or different.) Representative examples of polyarylene sulfide include polyphenylene sulfide (PPS), polyphenylene sulfide sulfone, polyphenylene sulfide ketone, etc. As the repeating unit of polyarylene sulfide, a p-arylene sulfide unit having the above formula (1) as Ar is preferable.

[0033] In addition, by using a resin containing, as the main structural unit of the polymer, preferably 60 mol % or more, more preferably 70 mol % or more, and even more preferably 80 mol % or more of p-phenylene units represented by the following structural formula (13), the polymer has excellent heat resistance and excellent strength when processed into fibers and wet-laid nonwoven fabrics.

[0034] [ka]

[0035] Furthermore, the polyarylene sulfide polymer may contain copolymerized units within the range that does not impair the effects of the present invention, but the copolymerized units are preferably contained in an amount of 20 mol % or less based on the polyarylene sulfide polymer.

[0036] The polyarylene sulfide fiber may contain various additives, such as inorganic substances such as titanium oxide, silica, barium oxide, and calcium carbonate, colorants such as carbon black, dyes, and pigments, flame retardants, fluorescent brighteners, antioxidants, and ultraviolet absorbing agents, within the scope of the invention.

[0037] The polyarylene sulfide fiber may be a single component fiber or a composite fiber in which two or more types of resins are composited. When the polyarylene sulfide fiber is a composite fiber, the composite form is not particularly limited as long as it does not impair the effects of the present invention, and can be appropriately selected from a core-sheath type, a sea-island type, a side-by-side type, an eccentric core-sheath type, a blend type, etc. The polyarylene sulfide contained in the polyarylene sulfide fiber is preferably contained in an amount of 70 mass% or more based on the total mass of the polymer in the fiber.

[0038] The cross-sectional shape of the polyarylene sulfide fiber is not limited in any way, and may be any irregular cross-sectional shape, such as a round cross section, a multi-lobal cross section such as a Y-shaped cross section or a triangular cross section, a flat cross section, an S-shaped cross section, a cross cross section, or a hollow cross section.

[0039] <Stretched polyarylene sulfide fiber> The wetlaid nonwoven fabric of the present invention contains stretched polyarylene sulfide fibers having an average fiber diameter of 0.3 μm or more and 3.0 μm or less. Here, the term "stretched polyarylene sulfide fibers" refers to fibers having an orientation parameter of 3.0 or more of polyarylene sulfide molecular chains. The orientation parameter is a value indicating the orientation of the molecular chains of polyarylene sulfide, and the larger the orientation parameter, the higher the orientation of the molecular chains. Here, the orientation parameter is measured using a laser Raman device. The orientation parameter of the stretched polyarylene sulfide fibers is preferably 3.0 or more, more preferably 5.0 or more, and even more preferably 7.0 or more. By setting the orientation parameter in the above range, the fibers have high heat resistance and excellent tensile strength. The orientation parameter of the stretched polyarylene sulfide fibers is preferably 40 or less, more preferably 30 or less, and even more preferably 25 or less. By setting the orientation parameter in the above range, the fibers have high elongation.

[0040] The orientation parameter in the present invention is obtained by the method described in the Examples. The orientation parameter of the drawn polyarylene sulfide fiber can be set to the above range by setting the draw ratio in the fiber drawing step to 2.5 times or more, but other methods may be used as long as they do not impede the object of the present invention.

[0041] The average fiber diameter of the stretched polyarylene sulfide fiber is 0.3 μm or more and 3.0 μm or less. If the average fiber diameter of the stretched polyarylene sulfide fiber is more than 3.0 μm, the number of fibers constituting the same basis weight is reduced, and the tensile strength of the wet nonwoven fabric is reduced, and the thickness of the wet nonwoven fabric is increased. In addition, if the average fiber diameter is large, the pore size variation increases and the uniformity of the pore size decreases. The average fiber diameter of the stretched polyarylene sulfide fiber is preferably 2.8 μm or less, more preferably 2.7 μm or less. On the other hand, if the average fiber diameter is less than 0.3 μm, the number of fibers constituting the same basis weight is increased, and the structure is such that the fibers are laid out, and the air permeability of the obtained wet nonwoven fabric is low. In addition, the aspect ratio is also increased, so the dispersibility is also reduced, and the uniformity of the pore size of the wet nonwoven fabric is reduced. The average fiber diameter of the drawn polyarylene sulfide fibers is preferably 0.5 μm or more, more preferably 1.0 μm. The average fiber diameter (μm) of the fibers mentioned here can be determined by the method described in the Examples.

[0042] The average fiber diameter of the drawn polyarylene sulfide fibers can be adjusted to the above range by adjusting the spinning discharge rate and the draw ratio, but other methods may be used as long as they do not impede the object of the present invention.

[0043] The aspect ratio of the stretched polyarylene sulfide fiber (average fiber length / average fiber diameter) is preferably 800 or more and 2000 or less. By making the aspect ratio of the stretched polyarylene sulfide fiber 2000 or less, stretched polyarylene sulfide fiber with excellent dispersibility can be obtained, and a wet nonwoven fabric with a more uniform pore size can be obtained. The aspect ratio of the stretched polyarylene sulfide fiber is more preferably 1800 or less, and even more preferably 1500 or less. On the other hand, by making the aspect ratio of the stretched polyarylene sulfide fiber 800 or more, the fibers are less likely to fall off during the processing step, and the tensile strength of the wet nonwoven fabric is further improved due to the entanglement between the fibers. The aspect ratio of the stretched polyarylene sulfide fiber is more preferably 900 or more, and even more preferably 1000 or more.

[0044] Here, the average fiber length can be measured based on "8.4.1. Average fiber length direct method (C method)" of JIS L1015:2010 "Testing methods for chemical fiber staples." Also, the aspect ratio is the value obtained by dividing the average fiber diameter of the fibers by the average fiber length.

[0045] <Undrawn polyarylene sulfide fiber> The wetlaid nonwoven fabric of the present invention preferably contains unstretched polyarylene sulfide fibers of 0.8 μm or more and 6.0 μm or less. Here, "unstretched polyarylene sulfide fibers" refers to fibers whose molecular chains are not oriented and have an orientation parameter of less than 3.0. The orientation parameter of the unstretched polyarylene sulfide fibers is preferably less than 3.0, more preferably 2.5 or less, and even more preferably 2.0 or less. By setting the orientation parameter within the above range, the fibers have many amorphous parts and have high adhesive ability when used as binder fibers.

[0046] The orientation parameter of the undrawn polyarylene sulfide fiber can be adjusted to the above range by setting the spinning speed to 1500 m / min or less, but other methods may be used as long as they do not impede the object of the present invention.

[0047] The average fiber diameter of the unstretched polyarylene sulfide fiber is 0.8 μm or more and 6.0 μm or less. When the average fiber diameter of the unstretched polyarylene sulfide fiber is larger than 6.0 μm, the number of fibers constituting the same basis weight is reduced, and the number of bonding points is reduced, so that the tensile strength of the wet nonwoven fabric is reduced and the wet nonwoven fabric becomes thicker. In addition, when the average fiber diameter is large, the pore size varies more and the uniformity of the pore size is reduced. The average fiber diameter of the unstretched polyarylene sulfide fiber is preferably 4.0 μm or less, more preferably 2.5 μm or less. On the other hand, when the average fiber diameter of the unstretched polyarylene sulfide fiber is less than 0.8 μm, the number of fibers constituting the same basis weight is increased, and the structure is such that the fibers are laid out, so that the air permeability of the obtained wet nonwoven fabric is reduced. In addition, the aspect ratio is also increased, so that the dispersibility is reduced and the uniformity of the pore size of the wet nonwoven fabric is reduced. The average fiber diameter of the undrawn polyarylene sulfide fibers is preferably 0.9 μm or more, and more preferably 1.0 μm or more.

[0048] The average fiber diameter of the undrawn polyarylene sulfide fibers can be adjusted to the above range by adjusting the spinning output and the draw ratio, but other methods may be used as long as they do not impede the object of the present invention.

[0049] The aspect ratio of the unstretched polyarylene sulfide fiber (average fiber length / average fiber diameter) is preferably 400 or more and 1800 or less. By setting the aspect ratio of the unstretched polyarylene sulfide fiber to more preferably 1600 or less, even more preferably 1400 or less, and most preferably 1300 or less, it is possible to obtain unstretched polyarylene sulfide fiber with excellent dispersibility, and it is possible to obtain a wet nonwoven fabric with high tensile strength with uniform binder adhesion points. Furthermore, by setting the aspect ratio to preferably 500 or more, even more preferably 700 or more, in addition to the fibers being less likely to fall off during the processing step, the fibers are easily entangled with each other, resulting in a wet nonwoven fabric with excellent tensile strength.

[0050] <Wet-processed nonwoven fabric> The wet nonwoven fabric of the present invention preferably contains stretched polyarylene sulfide fibers and unstretched polyarylene sulfide fibers. The stretched polyarylene sulfide fibers function as main fibers, and the unstretched polyarylene sulfide fibers function as binder fibers. The unstretched polyarylene sulfide fibers are mostly amorphous, and melt when heated to act as a binder. The stretched polyarylene sulfide fibers are stretched in the fiber manufacturing process, so that the fiber has high single fiber strength and excellent dimensional stability. In the present invention, by using stretched polyarylene sulfide fibers and unstretched polyarylene sulfide fibers in combination, it is possible to provide a wet nonwoven fabric having excellent chemical resistance and heat resistance. In addition, by forming a wet nonwoven fabric, a nonwoven fabric having a low basis weight and high uniformity of pore size can be obtained.

[0051] The wetlaid nonwoven fabric of the present invention preferably contains 20% by mass or more and 80% by mass or less of stretched polyarylene sulfide fibers relative to the total mass of the wetlaid nonwoven fabric. More preferably, it is 30% by mass or more and 70% by mass or less. When the stretched polyarylene sulfide fibers, which are the main fibers of the wetlaid nonwoven fabric, are 20% by mass or more, the wetlaid nonwoven fabric has higher tensile strength. On the other hand, when the stretched polyarylene sulfide fibers are 80% by mass or less, the proportion of binder fibers can be increased, and the number of bonding points between the main fibers increases, resulting in a wetlaid nonwoven fabric with higher tensile strength.

[0052] In addition, the wetlaid nonwoven fabric preferably contains 20% by mass or more and 80% by mass or less of unstretched polyarylene sulfide fiber relative to the total mass of the wetlaid nonwoven fabric. More preferably, it is 30% by mass or more and 70% by mass or less. When the unstretched polyarylene sulfide fiber, which is the binder fiber of the wetlaid nonwoven fabric, is 20% by mass or more, the number of bonding points increases, resulting in a wetlaid nonwoven fabric with higher tensile strength. On the other hand, when the unstretched polyarylene sulfide fiber is 80% by mass or less, the proportion of the main fiber component can be increased, resulting in a wetlaid nonwoven fabric with higher tensile strength.

[0053] In addition, other fibers may be mixed in as long as the effects of the present invention are not impaired, but the total amount of the stretched polyarylene sulfide fibers and the unstretched polyarylene sulfide fibers is preferably 80 mass% or more of the total mass of the wetlaid nonwoven fabric.

[0054] The mass mixing ratio of the stretched polyarylene sulfide fiber to the unstretched polyarylene sulfide fiber is preferably (stretched polyarylene sulfide fiber):(unstretched polyarylene sulfide fiber)=10:90 to 90:10, and more preferably (stretched polyarylene sulfide fiber):(unstretched polyarylene sulfide fiber)=20:80 to 80:20. By setting the ratio of the stretched polyarylene sulfide fiber to the unstretched polyarylene sulfide fiber as described above, the number of bonding points to the main fiber becomes appropriate, and a wetlaid nonwoven fabric having higher tensile strength can be obtained.

[0055] The average fiber diameter of the unstretched polyarylene sulfide fibers constituting the wetlaid nonwoven fabric of the present invention is preferably smaller than the average fiber diameter of the stretched polyarylene sulfide fibers. In the wetlaid nonwoven fabric of the present invention, the subject fibers (i.e., stretched polyarylene sulfide fibers) are bonded together via binder fibers (i.e., unstretched polyarylene sulfide fibers), and thus high stress is generated when the fabric is stretched. When the binder fibers are made thinner than the subject fibers, the bonded parts are multi-pointed and uniform, and stress is dispersed when the fabric is stretched, making the fabric less susceptible to plastic deformation, resulting in higher strength of the wetlaid nonwoven fabric. The ratio of the average fiber diameter of the unstretched polyarylene sulfide fibers to the average fiber diameter of the stretched polyarylene sulfide fibers (average fiber diameter of unstretched polyarylene sulfide fibers / average fiber diameter of stretched polyarylene sulfide fibers) is preferably 0.05 or more and 0.90 or less, more preferably 0.10 or more and 0.80 or less. By setting the thickness within the above range, the bonded joints are multi-pointed and uniform in structure, stress is dispersed when pulled, plastic deformation is resistant, and the tensile strength of the wetlaid nonwoven fabric is increased.

[0056] The wet nonwoven fabric of the present invention has through holes. Here, the through holes are formed by the gaps between the fibers. It is important that the average pore size is 0.5 μm or more and 50.0 μm or less. In the case of conventional wet nonwoven fabrics, if the diameter of the constituent fibers is simply made thinner to obtain a low basis weight, the wet nonwoven fabric cannot have a high uniformity of pore size and the tensile strength is reduced. Therefore, the present inventors have found that these problems can be solved by appropriately adjusting the average pore size. If the average pore size is less than 0.5 μm, the nonwoven fabric becomes film-like, making it difficult to maintain the porosity that is a characteristic of the nonwoven fabric, and the air permeability is reduced. The average pore size is preferably 1.0 μm or more, more preferably 3.0 μm or more. On the other hand, if the average pore size is too large and is greater than 50.0 μm, the wet nonwoven fabric tends to have poor texture, impair the uniformity of the pore size, and reduce the tensile strength. The average pore size is preferably 30.0 μm or less, more preferably 20.0 μm or less.

[0057] The average pore size referred to here refers to a value calculated by the bubble point method. For example, the porous material automatic pore size measurement system Perm-Porometer (manufactured by PMI) can be used for the bubble point method. In the measurement using this Perm-Porometer, a wet nonwoven sheet is immersed in a liquid with a known surface tension value, and gas pressure is supplied from above the sheet while increasing, and the average pore size is measured from the relationship between this pressure and the surface tension of the liquid on the surface of the wet nonwoven sheet.

[0058] The average pore size of the polyarylene sulfide wetlaid nonwoven fabric can be adjusted to fall within the above range by adjusting the basis weight and the average fiber diameter of the constituent fibers.

[0059] The basis weight of the wet-laid nonwoven fabric of the present invention is 1.0 g / m 2 More than 8.0g / m 2 The weight per unit area is less than 8.0g / m 2 If the weight is more than this, the wetlaid nonwoven fabric will be thick, and in addition, the number of constituent fibers will be too large, resulting in an extremely small pore size, which tends to reduce the air permeability and may result in a decrease in the ion-conducting properties of the electrolyte reinforced membrane.2 less than 5.0 g / m 2 less than 3.0 g / m 2 On the other hand, the basis weight is less than 1.0 g / m 2 If the number of fibers constituting the nonwoven fabric is less than 1.5 g / m, the tensile strength will decrease because the number of fibers constituting the nonwoven fabric will be too small. In addition, the pore size distribution will vary, and the uniformity of the pore size of the nonwoven fabric will decrease. 2 More preferably, 2.0 g / m 2 That's all.

[0060] The basis weight of the wetlaid nonwoven fabric can be adjusted to the above range by adjusting the amount of fiber added to the fiber dispersion for papermaking.

[0061] The thickness of the wetlaid nonwoven fabric of the present invention is preferably 15.0 μm or less. By setting the thickness to preferably 12.0 μm or less, more preferably 10.0 μm or less, and even more preferably 8.0 μm or less, the ion permeability of the electrolyte reinforced membrane using the wetlaid nonwoven fabric may be improved, which is preferable. In addition, when the wetlaid nonwoven fabric is mounted in a device as an electrolyte membrane reinforcement material, the volume occupied by the wetlaid nonwoven fabric is reduced, which allows the device to be made smaller and lighter.

[0062] The thickness of the wetlaid nonwoven fabric can be adjusted to the above range by adjusting the basis weight, the average fiber diameter of the constituent fibers, and the calendering conditions.

[0063] In the wetlaid nonwoven fabric of the present invention, when the pore size showing the maximum peak of the pore size distribution is defined as Dp (nm) in the pore size distribution curve, it is preferable that pores having 0.9 Dp or more and 1.1 Dp or less account for 50% or more of the total pores. Here, the pore size distribution curve is obtained from the pressure change (range of 0 kPa to 3000 kPa) of the air flow rate in the dry state and the wet state. More preferably, pores having 0.9 Dp or more and 1.1 Dp or less account for 55% or more of the total pores, and even more preferably, 60% or more. The higher the ratio of pores having 0.9 Dp or more and 1.1 Dp or less, the more uniform the pores are, and the less the deviation in the tensile strength and air permeability of the wetlaid nonwoven fabric becomes. The higher this value, the more desirable it is.

[0064] The ratio of pores having a Dp of 0.9 to 1.1 can be adjusted to the above range by adjusting the aspect ratio of the fibers, the concentration of the papermaking fiber dispersion, the concentration of the dispersant, and the concentration of the thickener.

[0065] The pore size distribution curve of the wetlaid nonwoven fabric of the present invention can be measured using a Perm-Porometer according to the bubble point method (ASTM F316-86).

[0066] The shrinkage rate of the wetlaid nonwoven fabric of the present invention after being kept at a temperature of 160°C for 24 hours and cooled to room temperature is preferably 8.0% or less. The shrinkage rate is more preferably 7.0% or less, and even more preferably 6.0% or less. The lower the shrinkage rate, the higher the dimensional stability against heat is, and when used as a reinforcing material for an electrolyte membrane operated at high temperatures for a long time, deterioration or tear of the membrane due to shrinkage is less likely to occur. Here, a negative shrinkage rate and expansion are also undesirable because they may cause deterioration or tear of the membrane. Therefore, a shrinkage rate of 0% or more is preferable.

[0067] In order to set the shrinkage rate within the above range, it is effective to subject the wet-laid nonwoven fabric to thermal crystallization. The thermal crystallization can be achieved by the method described below, but other methods may be used as long as they do not impede the object of the present invention.

[0068] The wet nonwoven fabric of the present invention preferably has a tensile strength of 0.50 N / 15 mm or more. The tensile strength is more preferably 0.55 N / 15 mm or more, even more preferably 0.60 N / 15 mm or more, and most preferably 0.80 N / 15 mm or more, so that breakage during the manufacturing process is unlikely to occur. In addition, the wet nonwoven fabric is unlikely to break even when tensile stress is applied during post-processing or during use. The tensile strength can be improved due to the fact that the stretched polyarylene sulfide fibers having high fiber strength are firmly bonded by the unstretched polyarylene sulfide fiber fusion parts. That is, by having the stretched polyarylene sulfide fibers and the unstretched polyarylene sulfide fiber fusion parts, the fibers are unlikely to come off, and the stretched polyarylene sulfide fibers bear the stress, etc., resulting in a wet nonwoven fabric having high tensile strength. The tensile strength of the wet nonwoven fabric in the present invention refers to a value measured by the method described in the Examples.

[0069] The air permeability of the wet-laid nonwoven fabric of the present invention is 3.0 cm 3 / (cm 2 s) or more. More preferably, it is 10.0 cm 3 / (cm 2 s) or more, particularly preferably 15.0 cm 3 / (cm 2 s). Air permeability is also necessary to ensure the properties of the nonwoven fabric. If the air permeability is high, ion conduction is less likely to be inhibited when the fabric is used as a reinforcing material for an electrolyte membrane, and ion conductivity tends to improve. On the other hand, if the air permeability of a wet nonwoven fabric is too high, dimensional stability decreases, so the air permeability should be set at 300 cm 3 / (cm 2 It is preferable that the thickness is less than or equal to s.

[0070] <Electrolyte-reinforced membrane> The wet nonwoven fabric of the present invention can be suitably used as an electrolyte membrane reinforcing material. In this case, the wet nonwoven fabric may be used as it is, or may be subjected to a hydrophilization treatment within a range that does not impair the effects of the present invention. By subjecting the wet nonwoven fabric to a hydrophilization treatment, the permeability of the electrolyte membrane is improved. Since the wet nonwoven fabric has excellent tensile strength and air permeability even when it is thin and has a low basis weight, it serves as an electrolyte membrane reinforcing material that has excellent ion permeation efficiency and is not easily broken during mounting or use.

[0071] The electrolyte-reinforced membrane of the present invention can be used by integrating the wet-laid nonwoven fabric of the present invention with an electrolyte membrane, and can be suitably used for fuel cell applications. Examples of electrolyte membranes include fluorine-based electrolytes and hydrocarbon-based electrolytes. Examples of fluorine-based electrolytes include perfluorosulfonic acid polymers, polytrifluorostyrene sulfonic acid polymers, and perfluorocarbon phosphonic acid polymers. In particular, cation exchange membranes made of perfluorosulfonic acid containing sulfonic acid groups, such as "Nafion" (registered trademark, DuPont), are preferably used because of their excellent basic properties.

[0072] <Wet-laid nonwoven fabric manufacturing method> The method for producing the wetlaid nonwoven fabric of the present invention will be described below.

[0073] [Production method of drawn polyarylene sulfide fiber] Various polyarylene sulfide fibers can be used, among which it is preferable to obtain the polyarylene sulfide fiber by disposing polyarylene sulfide in the island components and removing the easily soluble sea component polymer of the islands-in-sea type composite fiber having an islands-in-sea type composite cross section.

[0074] In this case, the manufacturing method is such that the polyarylene sulfide and the easily soluble polymer are melted separately, then passed through a polymer pipe and metered by a known metering device such as a gear pump. The polymers are then passed through a filter to remove foreign matter from the polymer, and then flowed into a spinneret. The respective polymers that flow into the spinneret are joined in an arbitrary composite form in the spinneret and discharged from the spinneret holes as islands-in-the-sea composite fibers.

[0075] The cross-sectional area of ​​the island components in the islands-in-sea type composite fiber can be adjusted by adjusting the polymer discharge rate. For example, by forming the island components of polyarylene sulfide into a round shape with a diameter of 2.0 μm, a round cross-section fiber with an average fiber diameter of 2.0 μm can be produced.

[0076] The discharged undrawn fibers are taken up by a roller (godet roller) rotating at a constant speed. The take-up speed is preferably 300 m / min or more to improve linear uniformity and productivity, and 1500 m / min or less to prevent the orientation of molecular chains.

[0077] The undrawn fiber thus obtained is subjected to a drawing step. Drawing is performed by running the fiber through a heated first roller or a heating device provided between the first roller and the second roller. The drawing conditions are determined by the mechanical properties of the undrawn fiber obtained, and the draw ratio is determined by the ratio of the peripheral speeds of the first roller and the second roller.

[0078] The temperature of the heated first roller or heating device in the drawing process is preferably 80° C. or higher and 130° C. or lower. By setting the temperature at 80° C. or higher, the drawing point is fixed and stable drawing is possible, and by setting the temperature at 130° C. or lower, yarn breakage can be suppressed and processability is improved. In addition, from the viewpoint of fixing the drawing point, the temperature of the second roller is preferably set to the temperature of the heated first roller or heating device + 20° C. or lower.

[0079] Furthermore, after passing through the second roller, the drawn fibers may be heated and heat-set by a heated third roller or a heating device provided between the second roller and the third roller. The heat-set temperature in the case of heat-setting is preferably 150 to 240°C. By setting the heat-set temperature to 150°C or higher, the shrinkage rate can be reduced by thermal crystallization. This can prevent the width of the nonwoven fabric product from becoming uneven during the wet-laid nonwoven fabric manufacturing process, and can provide a wet-laid nonwoven fabric with excellent dimensional stability.

[0080] The resulting fibers are then cut with a cutter to lengths of 0.3 mm to 10 mm to obtain cut fibers.

[0081] [Method for producing undrawn polyarylene sulfide fibers] Cut fibers of undrawn fibers can be obtained in the same manner as in the production method of drawn polyarylene sulfide fibers, except that drawing and heat setting are not carried out.

[0082] [Wet nonwoven fabric manufacturing method] The two types of cut fibers obtained by the above method are dispersed in an aqueous medium after dissolving the sea component with sodium hydroxide. Here, the aqueous medium refers to a liquid mainly composed of water. These dispersions are mixed in a desired ratio to obtain a papermaking dispersion. The fiber concentration in the dispersion is preferably 1.0 mass ppm or more and 80.0 mass ppm or less. By setting the fiber concentration to 1.0 mass ppm or more, more preferably 1.5 mass ppm or more, the production efficiency can be improved and the load of the dehydration process can be reduced. On the other hand, by setting the fiber concentration to 80.0 mass ppm or less, more preferably 60.0 mass ppm or less, and even more preferably 10.0 mass ppm or less, the dispersion state is improved, a uniform wet nonwoven fabric can be obtained, and the tensile strength of the wet nonwoven fabric can be increased.

[0083] The dispersion contains a dispersant, and the concentration of the dispersant in the dispersion is preferably 0.0010% by mass or more and 8.0% by mass or less. By setting the dispersant concentration to 0.0010% by mass or more, more preferably 0.0075% by mass or more, and even more preferably 0.010% by mass or more, the fibers are uniformly dispersed in the dispersion, the uniformity of the pore size of the obtained wet nonwoven fabric is improved, and the wet nonwoven fabric has a higher tensile strength. In addition, by setting the dispersant concentration to 8.0% by mass or less, more preferably 6.0% by mass or less, more preferably 3.0% by mass or less, and even more preferably 0.80% by mass or less, the fibers are uniformly dispersed in the dispersion, the uniformity of the pore size of the obtained wet nonwoven fabric is improved, and the wet nonwoven fabric has a higher tensile strength.

[0084] As the dispersant, a surfactant or the like can be used, and examples of the surfactant include cationic, anionic, and nonionic surfactants.

[0085] The papermaking fiber dispersion may contain a water-soluble polymer as a thickener, or a defoaming agent to suppress the generation of bubbles.

[0086] The papermaking dispersion prepared as above is made into paper using a cylinder, fourdrinier, or inclined wire papermaking machine or a hand-made papermaking machine, and the paper is dried using a Yankee dryer or rotary dryer to obtain a dry web. Then, a heat and pressure treatment is performed to obtain a wet nonwoven fabric. In the present invention, the heat and pressure treatment refers to the simultaneous application of heat and pressure, and is distinguished from a treatment such as drying in which only heat is applied without pressure. A dry web is a wet nonwoven fabric that has not been subjected to the heat and pressure treatment.

[0087] In a preferred method for producing the wetlaid nonwoven fabric of the present invention, it is preferable to produce the unstretched polyarylene sulfide fiber by heating and pressurizing treatment or the like in order to improve the adhesion between fibers. In this case, it is preferable to suppress crystallization during the manufacturing process of the dry web as much as possible. For this purpose, the drying temperature in the papermaking process is preferably 80 to 150°C, more preferably 90 to 140°C. It is also preferable to suppress crystallization by shortening the time of passing through the drying process. If the drying is insufficient, not only will the paper strength of the dry web decrease, but sudden thermal shrinkage will occur during the next heating and pressurizing process, making it easier for the paper to break. Conversely, if the drying is excessive, crystallization of the dry web will progress, making it difficult for the unstretched polyarylene sulfide fiber to undergo plastic deformation during the next heating and pressurizing process. As a result, the mechanical properties of the resulting wetlaid nonwoven fabric will decrease.

[0088] In the production of the wetlaid nonwoven fabric of the present invention, a dry web in which two types of cut fibers are mixed is subjected to a heat and pressure treatment. By the heat and pressure treatment, as described above, the unstretched polyarylene sulfide fibers are melted and softened, and polyarylene sulfide fused parts can be formed. Any means can be used for the heat and pressure application, and for example, a hot press with a flat plate or a hot calendar can be used. Of these, a hot calendar that allows continuous processing is preferred. As the rolls for the hot calendar, a metal-metal roll, a metal-paper roll, a metal-rubber roll, etc. can be used.

[0089] The temperature condition of the heat and pressure treatment is preferably a temperature equal to or higher than the glass transition temperature of the unstretched polyarylene sulfide fiber and equal to or lower than the melting point of the polyarylene sulfide fiber. For this purpose, the heating temperature is preferably set to 150 to 240°C. By setting the heating temperature to preferably 150°C or higher, the unstretched polyarylene sulfide fiber melts and softens, forming a polyarylene sulfide fused portion, and a wet-laid nonwoven fabric having excellent mechanical properties can be obtained. By setting the heating temperature to preferably 240°C or lower, the polyarylene sulfide fiber is completely fused, and the fiber shape can be prevented from being damaged.

[0090] When the calendering process is used as the heat and pressure treatment, the pressure is preferably 98 to 7000 N / cm. By setting the pressure to 98 N / cm or more, polyarylene sulfide fused parts can be formed, and a wet nonwoven fabric with excellent mechanical properties can be obtained. On the other hand, by setting the pressure to 7000 N / cm or less, the wet nonwoven fabric can be prevented from breaking during the heat and pressure treatment process, and the treatment can be performed stably. The process speed is preferably 1 to 30 m / min. By setting the speed to preferably 1 m / min or more, more preferably 2 m / min, good work efficiency can be obtained. On the other hand, by setting the speed to preferably 30 m / min or less, more preferably 20 m / min or less, heat can be conducted to the fibers inside the wet nonwoven fabric, and the binder fibers can be heat-fused. EXAMPLES

[0091] The wetlaid nonwoven fabric of the present invention will be described in more detail below with reference to the following examples. However, the present invention is not limited to these examples. Various modifications and amendments are possible without departing from the technical scope of the present invention. The respective property values ​​in the examples were determined by the following methods.

[0092] [Measurement and evaluation method] (1) Average fiber diameter The scanning electron microscope used was the "S-5500" manufactured by Hitachi High-Technologies Corporation, and the image analysis software was "WinROOF2015" manufactured by Mitani Shoji Co., Ltd., and measurements were performed as described below. Step 1: The cross section of the fiber is photographed using a scanning electron microscope. The observation magnification is as follows: when the fiber diameter is 5 μm or more and 14 μm or less, the observation magnification is 1000 times, when the fiber diameter is 1 μm or more and less than 5 μm, the observation magnification is 3000 times, and when the fiber diameter is less than 1 μm, the observation magnification is 5000 times. Step 2: Using the captured image and image analysis software, the area Af (μm 2 ) and calculate the diameter of a perfect circle that has the same area as this area Af. Step 3: This is measured for 100 randomly selected fibers, a simple number average is calculated to obtain the average fiber diameter (μm), and this is rounded off to the first decimal place.

[0093] (2) Average fiber length Based on "8.4.1. Average fiber length direct method (method C)" of JIS L1015:2010 "Test methods for synthetic fiber staples", measurements were taken and the average value of 200 fibers was calculated and rounded off to the first decimal place.

[0094] (3) Metsuke Based on JIS L1913:2010 "General nonwoven fabric test method", three 10cm x 10cm sample pieces are taken according to the mass per unit area, and the mass (g) of each is measured under standard conditions, and the average is calculated as 1m 2 Mass per unit (g / m 2 ) is expressed as

[0095] (4) Thickness In accordance with "9.3.1 Measurement of thickness" of JIS P8118:2014 "Paper and paperboard -- Test methods for thickness, density and specific volume", 20 test pieces of 10 cm x 10 cm were taken, and the thickness of each test piece was measured using a micrometer (manufactured by Mitutoyo Corporation), and the arithmetic average value was recorded as the thickness (μm).

[0096] (5) Tensile strength The tensile strength was measured according to "6.3.1 Standard time" of "6.3 Tensile strength and elongation (ISO method)" of JIS L1913:2010 "Test method for chemical fiber staples". Using Tensilon ("UTM-III-100" manufactured by Orientec Co., Ltd.), the maximum point load was measured under the conditions of a sample width of 15 mm, initial length of 20 mm, and a tensile speed of 20 mm / min. Five measurements were made for each level, and the arithmetic average value was calculated and used as the tensile strength (N / 15 mm).

[0097] (6) Average pore size The pore size was calculated according to the bubble point method (based on ASTM F-316-86) using a porous material automatic pore measurement system, Perm-Porometer (manufactured by PMI). The measurement sample diameter was set to 25 mm, and the pore size distribution was measured using Galwick (surface tension: 16 mN / m) as the measurement liquid with a known surface tension. The average flow diameter obtained by automatic calculation was used as the average pore size, and the value was rounded off to the first decimal place to use.

[0098] (7) Pore size distribution Using an automatic porous material pore measurement system, Perm-Porometer (manufactured by PMI), a wet nonwoven sheet was immersed in a liquid with a known surface tension value, and gas pressure was supplied from above the sheet while increasing, and measurements were taken in the order of dry-up and wet-up from the relationship between this pressure and the liquid surface tension on the surface of the wet nonwoven sheet to obtain a pore size distribution curve. In the obtained pore size distribution curve, the proportion of pores with a pore size Dp (nm) of 0.9Dp to 1.1Dp was calculated from all pores detected in the range of 0kPa to 3000kPa.

[0099] (8) Breathability According to JIS L1913:2010 "Test methods for synthetic fiber staples", "6.8 Air permeability (JIS method)", "6.8.1 Frazier type method", three 15cm x 15cm sample pieces were taken, and the air permeability of the three test pieces was measured at a test pressure of 125 Pa using an air permeability tester (TEXTEST AG "FX3300"), and the arithmetic average value was calculated as the air permeability (cm 3 / (cm 2 ·s)).

[0100] (9) Shrinkage rate A 15 cm x 15 cm wet nonwoven fabric in a free state was kept in a dryer at 160°C for 24 hours, and the shrinkage rate (%) was calculated from the dimensional change before and after the heat treatment using the following formula. Shrinkage rate = (1 - area of ​​wet nonwoven fabric after heat treatment / area of ​​wet nonwoven fabric before heat treatment) x 100.

[0101] (10) Orientation parameters Measurements were performed using a laser Raman device (Photon Design Co., Ltd.) as follows. First, a spectrum was obtained through a polarizer arranged in a polarization direction parallel to the polarization direction of the laser light. Next, the sample was rotated to obtain spectra in a polarization direction parallel to the polarization direction of the laser light and a polarization direction perpendicular to the polarization direction of the laser light. Then, the orientation parameter was calculated by the following formula. (orientation parameter) = (I 1080 / I 740 )(parallel) / (I 1080 / I 740 )(vertical) I 1080 / I 740 (Parallel): 1080 cm in the Raman spectrum measured with the polarization direction parallel to the fiber axis direction -1 The Raman band around 740cm -1 Divided by the intensity of the nearby Raman band. I 1080 / I 740 (Vertical): 1080 cm in the Raman spectrum measured with the polarization direction perpendicular to the fiber axis. -1 The Raman band around 740cm -1Divided by the intensity of the nearby Raman band.

[0102] [Production Example 1] <Production of drawn polyarylene sulfide fibers> Polyphenylene sulfide consisting only of p-phenylene sulfide units was used as the island component, and polyethylene terephthalate copolymerized with 5.0 mol% of 5-sodium sulfoisophthalic acid was used as the sea component. The island component was round in shape, and a sea / island component ratio of 40 / 60 was obtained by melt-extrusion using an islands-in-sea composite spinneret (1000 islands in total). The yarn was cooled and solidified, and then an oil agent was applied. The yarn was wound up at a spinning speed of 1000 m / min to obtain an undrawn fiber with an islands-in-sea composite cross section (single hole output: 2.6 g / min).

[0103] The resulting undrawn fiber was heated and drawn six times around a first roller and a second roller heated to 90°C and 100°C, respectively. It was then heated and drawn six times around a third roller heated to 180°C, and heat set. The draw ratio was 3.85 times, and the fiber was taken up by a non-heated roller at a peripheral speed of 400 m / min after the third roller to obtain a drawn polyphenylene sulfide fiber.

[0104] The resulting drawn polyphenylene sulfide fibers were then cut with a cutter to obtain cut fibers. The orientation parameter of the resulting drawn polyphenylene sulfide fibers was measured and found to be 11.

[0105] [Production Example 2] <Production of Undrawn Polyarylene Sulfide Fiber> After obtaining an undrawn fiber by the method described in <Production of drawn polyarylene sulfide fiber>, the obtained undrawn fiber was cut with a cutter to obtain a cut fiber. The orientation parameter of the obtained undrawn polyphenylene sulfide fiber was measured and found to be 2.5.

[0106] [Example 1] A fiber dispersion was obtained by dissolving the sea component from stretched polyphenylene sulfide fiber and unstretched polyphenylene sulfide fiber with the average fiber diameter and aspect ratio shown in Table 1 in a 3 mass% aqueous sodium hydroxide solution (bath ratio 1 / 100) heated to 90°C and 65°C, respectively. The fiber dispersion obtained was then weighed out so as to have the basis weight and mixture ratio shown in Table 1, and the fibers were dispersed so that the fiber concentration in the dispersion was 2.0 mass ppm, to obtain a fiber dispersion for papermaking. A dispersant (Y-258 (nonionic surfactant) manufactured by Yoshimura Oil Chemical Co., Ltd.) was added to this fiber dispersion for papermaking so that the dispersant concentration was 0.020 mass%, and a thickener ("Meipam" (registered trademark) manufactured by Meisei Chemical Industry Co., Ltd.) was added to the fiber dispersion for papermaking so that the dispersant concentration was 0.00030 mass%, and the mixture was thoroughly stirred. This fiber dispersion for papermaking was used to make paper using a square sheet machine (250 mm square) manufactured by Kumagai Riki Kogyo Co., Ltd., and the paper was dried in a rotary dryer with a roller temperature set to 120°C to obtain a dry web, which was then subjected to thermal calendaring at an iron roll surface temperature of 220°C, a linear pressure of 490 N / cm, and a roll rotation speed of 3 m / min to obtain a wetlaid nonwoven fabric, whose physical properties were evaluated. The evaluation results are shown in Table 1.

[0107] [Examples 2 to 22, Comparative Examples 1 to 8] A wetlaid nonwoven fabric was obtained in the same manner as in Example 1, except that various conditions were changed as shown in Tables 1 to 3.

[0108] As can be seen from the table, the wetlaid nonwoven fabrics of Examples 1 to 22 were thin but had high tensile strength and air permeability, and had high uniformity of pore size. In contrast, the wetlaid nonwoven fabrics of Comparative Examples 1 to 8 were poor in any one of the properties of thickness, strength, air permeability, or uniformity of pore size.

[0109] [Table 1]

[0110] [Table 2]

[0111]

Table 3

Claims

1. The stretched polyarylene sulfide fiber has an average fiber diameter of 0.3 μm or more and 3.0 μm or less, an average pore size of 0.5 μm or more and 50.0 μm or less, and a basis weight of 1.0 g / m 2 8.0g / m or more 2 and the average fiber diameter of the unstretched polyarylene sulfide fibers is smaller than the average fiber diameter of the stretched polyarylene sulfide fibers.

2. The aspect ratio (average fiber length / average fiber diameter) of the stretched polyarylene sulfide fiber is 800 or more and 2000 or less, 2. The wetlaid nonwoven fabric according to claim 1, wherein the unstretched polyarylene sulfide fibers have an aspect ratio (average fiber length / average fiber diameter) of 400 or more and 1,800 or less.

3. 3. The wetlaid nonwoven fabric according to claim 1, wherein, when the pore size showing the maximum peak of the pore size distribution in a pore size distribution curve is defined as Dp (nm), pores having a size of 0.9 Dp or more and 1.1 Dp or less account for 50% or more of all pores.

4. 3. The wetlaid nonwoven fabric according to claim 1, which has a shrinkage rate of 8.0% or less after being left to stand in an atmosphere at a temperature of 160°C for 24 hours.

5. An electrolyte-reinforced membrane comprising the wetlaid nonwoven fabric according to claim 1 or 2.

6. 2. The method for producing a wetlaid nonwoven fabric according to claim 1, comprising a step of dispersing the stretched polyarylene sulfide fibers and the unstretched polyarylene sulfide fibers in an aqueous medium to obtain a dispersion, wherein a fiber concentration in the dispersion is 1.0 ppm by mass or more and 80.0 ppm by mass or less.

7. The method for producing a wetlaid nonwoven fabric according to claim 6, wherein the dispersion contains a dispersant, and the concentration of the dispersant in the dispersion is 0.0010% by mass or more and 8.0% by mass or less.

Citation Information

Patent Citations

  • Wet-laid nonwoven fabric and method for producing the same

    JP2011106043A

  • Wet type nonwoven fabric containing polyphenylene sulfide fiber

    JP2020076174A

  • Filter medium for liquid filter and liquid filter

    WO2017159216A1

  • Solid polymer electrolyte reinforcing material and solid polymer electrolyte reinforcement using the same

    JP2003077494A

  • Base material for alkali water electrolysis diaphragm

    JP2016089197A